Impact of Social Determinants of Health on Postoperative Health-Related Quality of Life Among Patients Undergoing Colorectal Cancer Surgery - Tanaporn Thongdeebut; Suporn Danaidutsadeekul; Warunee Phligbua; Varut Lohsiriwat (Siriraj Medical Journal)
Objective: This study aimed to investigate the predictive effects of social determinants of health—specifically financial status, neighborhood environment, body mass index, anxiety, and family support—on the health-related quality of life (HRQoL) among patients undergoing colorectal cancer (CRC) surgery.